Clinicopathological investigations on mice envenomed with scorpion venom (Androctonus amoreuxi) - Hamedy, A F; Kilany, Omnia E; Mohallal, Mahmoud E; Soliman, Belal A; Shoukry, Nahla M; Khaled, Howayda S (Journal of the Egyptian Society of Parasitology, 2012)
The present study assessed the toxicity of Androctonus amoreuxi crude venom on blood and biochemical serum parameters of mice. Adult male Albino mice were divided into three groups, in the control group mice were injected S.C. with saline solution. The second group and the third were injected with the venom S.C. in mice in the following doses 1/4 and 1/2 dose of LD50 respectively. Blood and serum samples were taken after 3 hours, 6 hours, 9 hours, 12 hours, 4 days and 7 days. Hematocrit (Ht), red blood cells (RBC) count, hemoglobin, MCV, MCH & MCHC were performed. Serum biochemical parameters, the levels of total proteins, albumin, globulin, glucose, cholesterol, triglycerides, ALT, AST, ALP, creatinine, uric acid and urea were measured. RBCs, Hob, PCV, MCV, MCH & MCHC showed significant increase, and increase in total protein, albumin and globulin within the experiment. Glucose and cholesterol levels were significantly increase from the beginning. Triglycerides showed significant decrease after 6 hours. Liver enzymes and kidney functions revealed significant changes post-injection.